Developing and Improving Purification Strategies for New Biopharmaceuticals - Fernandes, Rita Patrício (2022)
The demand for new biopharmaceuticals has grown considerably in the last decade, with their use in applications such as vaccination, gene therapy and oncolytic therapy. However, this new class of biologics also brings additional complexity reflected with both upstream and downstream processing. One concern regarding insect-cell based biopharmaceuticals produced using the baculovirus expression vector system (BEVS) is the co-production of baculovirus. Their rod-shaped form and their similar size with virus-like particles (VLPs) increase the difficulty in discriminating between them. With this challenge in mind, this dissertation presents a purification strategy based on an impurity-focused affinity chromatography approach for baculovirus removal. Four affinity ligands (BV-2, BV-3, BV-6, and BV-8) were selected according to their selectivity for baculovirus removal. The selected ligands were immobilized in chromatographic resins and the dynamic binding capacities for the different prototypes were determined as well as the impact of the residence time (0.3, 1, 2 and 4 min). The best compromise between influenza VLPs yield and baculovirus removal was observed with a residence time of 1 minute, with BV-2 and BV-3 ligands showing the best performance. As a proof-of-concept, BV-2 and BV-3 selectivity for baculovirus was also evaluated using different biopharmaceuticals produced using the baculovirus expression system: hepatitis C VLPs and adeno-associated virus (AAV) systems. Results show that it is possible to achieve more than 3 log reduction value of baculovirus in AAV system and 2 log for hepatitis C VLPS system. The recovery of AAVs and hepatitis C VLPs was close to 60% in BV-2 ligand. The ligand prototypes resins shown also to be robust to harsh elution and cleaning conditions, maintaining the same baculovirus removal over 20 cycles. Overall, this thesis contributed to the development of insect cell-based biopharmaceuticals manufacturing by exploiting a new affinity-based approach, with promising results in baculovirus removal.